The sociospatial metamorphosis resulting from milk production increment: an analysis of this activity in the city of Ituiutaba/MG during the period of 1960 to 2013 - Souto, Thales Silveira; Bezzi, Meri Lourdes (Sociedade & Natureza, 2016)
he dairy industry has obtained considerable growth in Ituiutaba/MG from the implementation of a milk processor multinational unit in 1974, as also due to the existence of demand for other dairy agribusiness, increasing milk production to 325.3% from 1975 to 2013 (IBGE, 2013). In this perspective, the aim was to analyze the socio-spatial transformations resulting from the expansion of milk production in Ituiutaba, from 1960 to 2013. Specifically, we sought to (a) understand the barriers for the development of this sector in the Brazilian agricultural scene; (b) verify the importance of the development of industrial milk processing units in Ituiutaba for maintenance and/or growth of the productive sector; and (c) know the reality experienced by the dairy producer in Ituiutaba. Methodologically, the research was developed in steps. In the first step was done the bibliographic research Subsequently it was collected secondary data from Ituiutaba’s agricultural production within the timeline from 1960 to 2013, using the Agricultural sense of 1960 and the agriculture and husbandry sense of 1970, 1980, 1996 and 2006 from the Brazilian Institute of Geography and Statistics - IBGE and other databases available in the IBGE website. The third phase is related to the development of field work. It was conducting interviews with the subjects. In the last step, we analyzed and interpreted the information collected, resulting in an understanding of the transformations proceeded from the increment of dairy production in Ituiutaba.